Excited States of Xanthene Analogues: Photofragmentation and Calculations by CC2 and Time‐Dependent Density Functional Theory. Issue 19 (18th August 2016) - Kulesza, Alexander Jan; Titov, Evgenii; Daly, Steven; Włodarczyk, Radosław; Megow, Jörg; Saalfrank, Peter; Choi, Chang Min; MacAleese, Luke; Antoine, Rodolphe; Dugourd, Philippe
Abstract: Action spectroscopy has emerged as an analytical tool to probe excited states in the gas phase. Although comparison of gas‐phase absorption properties with quantum‐chemical calculations is, in principle, straightforward, popular methods often fail to describe many molecules of interest—such as xanthene analogues. We, therefore, face their nano‐ and picosecond laser‐induced photofragmentation with excited‐state computations by using the CC2 method and time‐dependent density functional theory (TDDFT). Whereas the extracted absorption maxima agree with CC2 predictions, the TDDFT excitation energies are blueshifted. Lowering the amount of Hartree–Fock exchange in the DFT functional can reduce this shift but at the cost of changing the nature of the excited state. Additional bandwidth observed in the photofragmentation spectra is rationalized in terms of multiphoton processes. Observed fragmentation from higher‐lying excited states conforms to intense excited‐to‐excited state transitions calculated with CC2. The CC2 method is thus suitable for the comparison with photofragmentation in xanthene analogues. Abstract : Falling to pieces : The nano‐ and picosecond laser‐induced photofragmentation spectra of xanthene analogue dyes are recorded. The photophysics, including the multiphoton absorption of these systems, are analyzed with excited‐state computations by using the CC2 method and time‐dependent density functional theory.